2001
DOI: 10.1161/01.str.32.7.1499
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Incidence and Case Fatality Rates of Aneurysmal Subarachnoid Hemorrhage in Izumo City, Japan, Between 1980–1989 and 1990–1998

Abstract: Tetsuji Inagawa, MDBackground and Purpose-With aging of the population, the profile of subarachnoid hemorrhage (SAH) is likely to change; however, evaluation of long-term trends for incidence and case fatality rates of SAH is still limited. Methods-We compared the incidence and case fatality rates of aneurysmal SAH during the 9-year period 1990 -1998 with those during the 10-year period 1980 -1989 in Izumo City, Japan. Results- During 1980During -1989During and 1990During -1998, we diagnosed 170 and 188 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
2
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 88 publications
(118 reference statements)
3
109
2
4
Order By: Relevance
“…SAH was thought to be due to aneurysm rupture in more than 97% of patients based on their medical history. The crude annual incidental rate of SAH in the present study was 18 per 100 000, which is similar to the previously reported annual age-and sex-adjusted incident rates of 23 and 15.5 per 100 000 in Japan, 10,25) so the patients in this study may be representative of the community population. Climate changes such as daily temperature, humidity, and atmospheric pressure have been proposed to influence seasonal patterns of SAH occurrence in previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…SAH was thought to be due to aneurysm rupture in more than 97% of patients based on their medical history. The crude annual incidental rate of SAH in the present study was 18 per 100 000, which is similar to the previously reported annual age-and sex-adjusted incident rates of 23 and 15.5 per 100 000 in Japan, 10,25) so the patients in this study may be representative of the community population. Climate changes such as daily temperature, humidity, and atmospheric pressure have been proposed to influence seasonal patterns of SAH occurrence in previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…Although SAH severity (distribution of WFNS grades at presentation) was comparable in OXVASC and OCSP (figure e-1), a greater proportion of patients surviving to reach hospital underwent vascular imaging in OXVASC compared to OCSP (24 [11][12][13][14][15][16], p ϭ 0.001). In OCSP, all 5 treated aneurysms were secured by surgical clipping, whereas in OXVASC, 15/18 (83%) treated aneurysms were secured by endovascular embolization.…”
Section: Systematic Reviewmentioning
confidence: 96%
“…13,14,16,[19][20][21]36 Data from the Perth Community Stroke Study from June 1995 to June 1996 19 were published separately from data from December 1996 to February 1998, 29 but these were combined for this analysis because the periods of study were so close. A pooled analysis of time trends within study populations, based on the difference in 1-month casefatality taken from the 2 furthest available timepoints (figure 2), demonstrated a 0.9% reduction in casefatality per annum (0.2-1.6, p ϭ 0.01).…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Fourth, the observed differences may reflect racial differences in the patient population because recent genetic analyses indicated that Japanese and/or Finnish patients are at a higher risk of rupture. 17,25 Hence, the external validity applies only to a Japanese population and may not be generalizable to other ethnic groups. Finally, we performed 22 univariate analyses, with data presented in Tables 1 and 2.…”
Section: Limitationsmentioning
confidence: 99%